Determinants of city-level private car ownership: Effect of vehicle regulation policies and the relative price. (January 2022) - Yang, Hongtai; Zhai, Guocong; Liu, Xiaohan; Yang, Linchuan; Liu, Yugang; Yuan, Quan
Abstract: Despite many prior studies about the determinants of city-level private car ownership in China, limited studies investigate the effects of vehicle regulation policies and relative price (the ratio of the average car price to GDP per capita) on city-level private car ownership simultaneously. Thus, panel data of 212 cities in China from 2006 to 2015 were collected to explore these effects. The potential explanatory variables include relative price, vehicle regulation policies, socio-economic factors, urban characteristics of the city, and transportation-related factors. The pooled model, fixed-effects model, and random effects model are constructed to analyze the panel data. With the fixed effect on the temporal trend, the fixed-effects model turns out to be the best. Variables including relative price, license plate lottery, vehicle use restriction based on the last digit of the license plate, the average salary of employed workers, and the number of taxis per 10, 000 population are all found significant. Supportive policies for alternative fuel cars do not significantly affect private car ownership. One percent increase in the relative price is associated with a 0.08% decrease in private car ownership. The license plate lottery and vehicle use restriction policies would reduce private car ownership by 18.94% and 7.7%, respectively. The finding of this study could provide a helpful reference for policymakers to develop appropriate measures to control the growth of private car ownership of a city. Highlights: Determinants of city-level car ownership are revealed based on data of 2006–2015. Pooled OLS model, fixed-effects model, and random-effects model are compared. Supportive policies for alternative fuel vehicles do not influence car ownership. 1% increase in relative car price is related to 0.08% decrease in car ownership. Implementation of vehicle use restriction leads to 7.7% decrease in car ownership.